Improving Literacy and Numeracy Skills at SD Negeri 173616 Lumban Ruhap Through Campus Teaching Program Class 3 - Ineke Junita LumbanTobing; Surya Darma Pardede; Sanggam Pardede; Tarida Ilham Manurung; Relinda Sidabutar (Eumpang Breuh : Jurnal Pengabdian Masyarakat, 2022)
The Independent Learning Campus Independent Program (MBKM) is one of the programs organized by the Ministry of Education and Culture. The Campus Teaching Program is one of the programs in the Merdeka Learning Campus Merdeka Program which aims to teach, assist technology, and assist school administration and teachers. One of the schools targeted for the Teaching Campus program is SD Negeri 173616 Lumbanruhap which is located in Lumbanruhap Village, Habinsaran District, Toba Regency, North Sumatra Province. In this Teaching Campus program, students who are appointed to take part in the program have the responsibility of assisting the school in the teaching process, assisting adaptation to technology, and assisting school administration. In addition, Campus Teaching students have a responsibility to improve student character and increase student interest in learning during this pandemic. The purpose of student participation in the Teaching Campus program is a process of adding relationships, adding experiences outside the world of lectures, developing students' insight, character and soft skills, encouraging and spurring national development by fostering student motivation to participate in development, as well as increasing the role and the real contribution of universities and students in the development of education in Indonesia.